The prognostic value of the platelet-to-lymphocyte ratio in multiple myeloma patients treated with a bortezomib-based regimen - Quane Zhang; Yifan Wang; Wenting Shi; Yue Chen; Zhengmei He; Liang Yu; Chunling Wang (Scientific Reports)
Abstract Multiple myeloma (MM) is the second most common hematological malignancy. Previous studies have validated the prognostic significance of the platelet-to-lymphocyte ratio (PLR) in patients with certain solid tumors. However, the relationship between the PLR and prognosis in myeloma patients has not been clearly demonstrated. In our study, we included 122 newly diagnosed MM patients who were treated with bortezomib-based chemotherapy. These patients were divided into low-PLR and high-PLR groups based on their initial PLR values. We compared the clinical characteristics between the two groups and utilized restricted cubic splines (RCSs) in the regression model to estimate the nonlinear relationship between the initial PLR and overall survival (OS) in MM patients. The results showed that patients in the low-PLR group had significantly worse OS (P = 0.00031) and progression-free survival (PFS) (P < 0.0001) compared to those in the high-PLR group. Furthermore, within the higher-risk MM group, a low PLR was also associated with worse OS (P = 0.0037) and PFS (P = 0.0048). Therefore, a low PLR was identified as an independent predictor of poor OS in MM patients. The RCS curves further confirmed a significant nonlinear relationship between the PLR and OS in patients with MM. The PLR may serve as a significant independent prognostic indicator for MM patients undergoing bortezomib-based chemotherapy, and there exists a crucial nonlinear relationship between the PLR and OS in these patients.